ANALYSIS OF THE EFFICIENCY OF APPLICATION OF THE TWO SURGERY METHODS OF TREATMENT OF THE URETHRAL INJURY CONSEQUENCES - S.S. ZIYOZODA; G.M. KHODZHAMURADOV; KH.KH. RIZOEV; M.M. ISMOILOV; M.B. SHARIPOVA; A.KH. TOLIBOV (Avicenna Tajik State Medical University, 2021)
Objective: To analyze the results of application of the two surgical techniques in the treatment of the consequences of urethral injuries (CUI). Methods: 38 patients aged 16.4±1.9 years with CUI were examined. CUI were localized in the area of the scaphoid fossa (n=3), the penile part (n=9), the bulbous region (n=6). Multi-site and panurethral lesions were noted in 8 and 12 cases, respectively. Additional research methods included ultrasound examination of the bladder, uroflowmetry, residual urine measurement, and, if necessary, retrograde and voiding urethrography. The patients underwent two types of surgical intervention: one-stage (16 patients, 1st group) and two-stage (22 patients, 2nd group) urethroplasty using a buccal mucosal flap. The results of surgery were assessed by ascending urethrography and uroflowmetry. The follow-up period ranged from 6 to 24 months. Results: The immediate and long-term results between the two groups showed significant difference. According to uroflowmetry data, the main indicator of the effectiveness of surgical intervention was a stable retention of maximum urine flow rate at least 15 ml/sec. In the 1st group, there was one case of early wound dehiscence with the formation of a fistula. In the 2nd group, early divergence was observed in 8 cases, it was also accompanied by formation of fistulas. These complications required additional surgical intervention; their correction was deferred. Conclusion: One-stage urethroplasty using a buccal mucosal flap for CUI proved to be safer and more effective compared to the two-stage technique